Surdez, cultura e identidade: as trajetórias sociais na construção das identidades de indivíduos surdos - Ferrari, Carla Cazelato (2017)
The purpose of this study was to understand how the objective social conditions of deaf people, together with their biological conditions, expressed in diverse social trajectories, favored the construction of social identities, having as the differentiation parameter decision of these people in preferably use oral language or the language of signs. In this way, in the wake of studies developed by Bueno (1997, 2011), explicitly in contrast to the current sócioantropológica or deaf studies, that principle is the existence of a "deaf culture", expressed by the use of brazilian sign language and the resulting construction of a "deaf community" in antagonistic culture dominant listener position. The basic procedures used for data collection were, first through a questionnaire which mapped out the profile of 24 deaf people, as regards personal and family characteristics, education, social origin and professional profile, followed by interviews with six of these agents. Were used as theoretical contributions of Pierre Bourdieu (1996, 1998, 2003), with regard to social classification concepts, strategies and trajectories, and Williams (1992, 2011a, 2011b) with respect to the concept of culture. In the field of special education, take as a reference the critical studies of education of deaf people initiated by Bueno (1997, 2011) and composed by authors such as Mendonça (2007), Silva (2011), Botarelli (2014) and others. The study pointed out that the appropriation and predominant use of sign language or oral language was not the only element that constituted the social identity of the six individuals interviewed, as well as the appropriation and predominant use of one of the two languages, was also not the only vector responsible for the social integration of those individuals. The constitution of social identity and the preferred usage for sign language or oral language is given in the course of the social trajectory of the deaf agent, according to the social position he occupied in certain social spaces and historic moment, as well as social relations he established